Effect of modified housing on behavioural and physiological responses of crossbred cows in hot humid climate - SINHA, RANJANA; KAMBOJ, M L; RANJAN, ASHISH; LATHWAL, S S (The Indian Journal of Animal Sciences, 2017)
The present study was carried out to investigate the effect of modified housing on behavioural and physiological responses of 16 lactating cows during hot humid season. Data on various parameters such as activity patterns of feeding, rumination, lying and standing time, rectal temperature, respiration rate, pulse rate and skin temperature were recorded. Analysis revealed that cow comfort, resting time, time spent on feeding and rumination weresignificantly higher in modified shed (G2) as compared to existing loose shed (G1). Respiration and pulse rate were significantly lower in G2 as compared to G1. Frequency of lying bouts significantly decreased while the duration of lying bouts increased in G2 as compared to G1 group. It was concluded that the cows housed in modified shed were more comfortable and had improved physiological reactions and behavioural responses during hot-humid season as compared to cows housed in existing shed.